Ḥafriyyatu ’l-’Anṣārī fī Ḥalab, ‘aṣru ’l-burūnzi ’l- qadīmu wa ’l-’awsaṭu - Sulауmān, ’Anṭuwān
Excavations at al-’An??r? in Aleppo, the Old (i.e. Early) and Middle Bronze Ages; ersch. 1986; Arabic section; in Arabic; 188-189: cylinder seal.